DYRENE, DER IKKE BURDE EKSISTERE - Thomas, Lars (Tidsskriftet Antropologi, 1997)
Lars Thomas: The Animals that Shouldn’t Exist Strange and fantastic animals have always been a part of human society. They lurk in the comer of our eyes, when we walk through a forest late at night, or pass through a cemetery. Today most of these creatures have been banished to the realm of fantasy but, according to the modem science of cryptozoology, some of the strange and supposedly imaginary beings that are still seen today, might be real animals, so far not recognized by conventional zoological science. Cryptozoologists study three different types of animals: 1. Common species seen in places where they shouldn’t or couldn’t be. 2. Well-known, but supposedly extinct species still being seen. 3. Supposedly fantastic or mythological beings that might be real. Most conventional zoologists are very sceptical towards these animals, possibly because they challenge the normally accepted view of the natural world.